Between darkness and light: spring habitats provide new perspectives for modern researchers on groundwater biology - Manenti,Raoul; Piazza,Beatrice (PeerJ, 2021)
Springs are interfaces between groundwater and surface habitats and may play an important role in the study of subterranean animals. In this systematic evidence review and meta-analysis, we explore whether observations of stygobionts in springs are relevant and more common than observations of epigean animals in groundwater. We searched the Web of Science database for papers on groundwater fauna and spring fauna. For each paper we found, we recorded whether the paper reported the occurrence of typical stygobionts in springs, of surface animals in groundwater, or of the same taxa in both habitats. If so, we recorded how many such species were reported. We also recorded the scientific discipline of each study and the year of publication. Our search yielded 342 papers. A considerable number of these papers reported stygobionts in springs: 20% of papers dealing with groundwater fauna and 16% of papers dealing with spring fauna reported the occurrence of stygobionts in spring habitats. Both the number of papers that mentioned stygobionts in springs, and the number of stygobiont species that were documented in springs, were higher than equivalent measures for the occurrence of surface fauna underground. We also detected a positive relationship between year of publication and the number of reports of stygofauna in springs. To broaden the insights from biological research on underground environments, we suggest that springs should be considered not only as simple sampling points of stygobionts but also as core stygobiont habitats.
Keywords: Seepage; Source; Shallow subterranean habitats; Adaptation; Subterranean biology; Cave